Poisoning of glutaraldehyde-containing products: clinical characteristics and outcomes - Suthimon Thumtecho (2022)
Objective: This study describes the clinical characteristics, outcomes, and factors at presentation associated with death of cases poisoned by glutaraldehyde (GA)-containing products. Methods: We performed a 5-year retrospective cohort study (July 2013–June 2018) using data from the Ramathibodi Poison Center. Results: There were 244 cases included in this study. Most were men with a median age of 37 years. The GA-containing products were mainly used as farm disinfectants (99.2%), with a median concentration of 15%. Most products (76.2%) contained co-formulants such as cationic detergents and formaldehyde. Most circumstances were accidental (56.9%). The others were suicide attempts by ingestion, except one patient who intentionally injected GA subcutaneously. The most common route of exposure was ingestion (95.0%). Local symptoms in areas of exposure were common. Ingestion resulted in more severe local effects than other routes, and corrosive effects occurred in 23 cases (9.4%). Systemic signs and symptoms occurred in 149 patients (61.1%). Systemic effects included abnormal vital signs, desaturation, altered mental status, hypo/hypernatremia, hypokalemia, low bicarbonate/metabolic acidosis, acute kidney injury (AKI), hepatitis, and rhabdomyolysis. Systemic effects mostly resulted from ingestion. Most patients had mild severity, received only supportive treatment, and fully recovered. The median length of hospital stay was 2 days. The one case of subcutaneous injection developed both local and systemic effects but survived. The mortality rate was 3.7%. Multivariate analysis indicated that either neurological symptoms or AKI at presentation were associated with death. Conclusions: In our study, patients were exposed to GA-containing products that were mainly used as farm disinfectants and were generally co-formulated with other substances. Poisoning with these products commonly resulted in mild local irritative symptoms. However, some cases developed corrosive symptoms, systemic effects, or even died. As neurological symptoms or AKI could prognosticate deaths; physicians should look for these factors in patients with GA exposure at presentation for close monitoring and aggressive treatment.